TODDLER SOCIOEMOTIONAL BEHAVIOR IN A NORTHERN PLAINS INDIAN TRIBE: ASSOCIATIONS WITH MATERNAL PSYCHOSOCIAL WELL‐BEING. Issue 1 (8th November 2013) - Frankel, Karen A.; Croy, Calvin D.; Kubicek, Lorraine F.; Emde, Robert N.; Mitchell, Christina M.; Spicer, Paul
ABSTRACT M.C. Sarche, C.D. Croy, C. Big Crow, C. Mitchell, and P. Spicer (2009) provided first‐ever information relating the socioemotional development of American Indian toddlers to the immediate context of their mothers' lives. The current study sought to replicate and build on their earlier work by examining the impact of additional maternal risk factors, identified in previous research with non‐American Indian populations, on the development of American Indian toddlers: maternal depression, negative social influences, and mother's feelings of isolation. At 27 months, American Indian mothers (N = 110) completed the Parent Demographic Questionnaire, which measured maternal psychosocial characteristics (e.g., depressed affect, social support, drug and alcohol use, isolation) and demographics. Mothers also completed the Infant–Toddler Social Emotional Assessment (A.S. Carter & M.J. Briggs‐Gowan, 2006) and the Parent–Child Dysfunctional Interaction subscale of the Parenting Stress Index (R.R. Abidin, 1995, 1997). Some results replicated the original study, but others did not. Reports of a dysfunctional mother–child relationship related to externalizing and internalizing problems, replicating the earlier study. This study also found associations between a dysfunctional mother–child relationship and socioemotional competence as well as dysregulation. The previous finding of a relationship between American Indian identity and socioemotional competence was supported. Adding the effects of maternal depressed affect and isolation significantly increased prediction of toddler behavior problems.